Pengaruh Gaya Kepemimpinan dan Komitmen Organisasi Kader PKK Terhadap Kinerja di Tim Penggerak PKK Desa Gogik Kecamatan Ungaran Barat - Umi Fadlilah Hidayanti; Yoki Nawan Gunara; Heru Yuliyanto (Dharma Ekonomi, 2024)
This study aims to analyze the influence of leadership style and organizational commitment on the performance of PKK cadres in the PKK Mobilization Team of Gogik Village, West Ungaran District. The participants in this study were active PKK cadres involved in organizational activities. The research employed a quantitative approach using multiple linear regression analysis to examine the relationship between the independent variables—leadership style and organizational commitment—and the dependent variable—cadre performance. The findings indicate that leadership style has a positive and significant impact on the performance of PKK cadres. Additionally, organizational commitment plays a crucial role in improving cadre performance. These results suggest that effective leadership and strong cadre commitment contribute to enhancing overall organizational performance. Therefore, improving leadership quality and strengthening cadre commitment should be prioritized in organizational management to achieve more optimal PKK program objectives.